Pengelolaan Dana Desa Dalam Proses Peningkatan Ekonomi Desa - Ratu Adinda Nurtafdhilla; Effendi Hasan (Jurnal Ilmiah Mahasiswa Fakultas Ilmu Sosial & Ilmu Politik, 2022)
One of the government's efforts to achieve economic equity throughout all regions of Indonesia is through the village fund allocated in the State Revenue and Expenditure Budget. The village fund was rolled out in 2015 to all provinces in Indonesia, including Aceh. One of the villages in Aceh that receives village funds is Desa Alue Naga. This village has realized good development using village funds during 2015-2020. However, the village funds have been used to build infrastructure to support community economic activities. The Purposes of village funds are; to improve public services in villages, alleviate poverty, improve the village economy, reduce development gaps between villages, and strengthen rural communities as development subjects. This study animed to identify the management of village funds and the obstacles faced in improving the economy of Desa Alue Naga, Syiah Kuala Subbdistrict, Banda Aceh. This Study was qualitative descptive research. The data were collected through interviews as field data, then analyzed according to the research focus using financial village management theory to explain the village funds management and the obstacles faced. The findings revealed that Desa Alue Naga succeeded in establishing a Refill Drinking Water Depot as Village-Owned Enterprises (BUMG) using village funds provided by the government. Desa Alue Naga has also set up a Micro Small and Medium Enterprises (UMKM) of boat docking to create jobs for the local community. The obstacles faced in improving the economy village of Desa Alue Naga were: a lack of seriousness from the owners of Micro and Small Enterprises (UMKM) in running their business and lack of human resources in managing village funds. In addition, the villages consultative body (Tuha Peut Gampong) and the village head had strained relations that slows down the disbursing of village funds.